Excess power rerouting in the grid system during high penetration solar photovoltaic - Kamil K.; Chong K.H.; Hashim H. (Elsevier Ltd, 2024)
Large scale solar PV plant has been actively implemented in many countries. One of the concerns on this implementation is imbalance supply and demand which resulting power congestion that might cause instability of power system operation. This paper presents the algorithm to solve power congestion in the power line during high penetration solar photovoltaic (PV) to the grid. In this study the optimization approach is done using Multiple mitosis genetic algorithm (MMGA) to choose the best line to receive the excess power from the congested line and the system used to test the algorithm for 3 different scenarios is IEEE 30 bus test systems. Power flow simulation is done using Power system simulation for engineers (PSSE) software. Simulation results show that the excess power exist in the power line during high penetration solar PV are solved by rerouting the excess power to the available best adjacent line found using MMGA. This study is useful to the planning division of power system engineer to consider the option to avoid power congestion in the grid before the integration of large-scale solar farm. 2022